Giant phonon anomaly in topological nodal-line semimetals - Zizhen Zhou; Xiaolong Yang; Honghui Wang; Guang Han; Xu Lu; Guoyu Wang; Rui Wang; Xiaoyuan Zhou (Fundamental Research)
The band topology has been revealed to bring a wide array of novel electronic transport phenomena, but its interaction with phonon properties remains largely unexplored. Here we propose that continuous topological singularities with variable Fermi wave vectors can lead to giant effects on phonon transport in nodal-line semimetals. Using first-principles calculations, we show that such an exotic feature is present in a well-known topological semimetal ZrSiSe, in which the unique nodal-line can guarantee considerable momentum-continuous phonons to satisfy the stringent condition of Kohn anomaly and thereby dramatically strengthen the electron-phonon coupling. Moreover, the momentum-continuous anomaly phonons with eight arms of vertical Fermi surface drive intense phonon-electron scattering that is even comparable with intrinsic phonon-phonon scattering, giving rise to a reduction of ∼45% on room temperature lattice thermal conductivity. Our findings not only uncover giant phonon anomaly in topological nodal-line semimetals but also provide guidance for exploring the vital influence of electronic band topology on thermal transport bridged by the electron-phonon coupling.